Geographical stratification by socio-economic status: methodology from a household survey with elderly people in S. Paulo, Brazil Estratificação geográfica por nível sócio-econômico: metodologia utilizada em um inquérito domiciliar com idosos residentes em São Paulo, Brasil - Luiz Roberto Ramos; Samuel Goihman (Universidade de São Paulo, 1989)
Considering that in most developing countries there are still no comprehensive lists of addresses for a given geographical area, there has always been a problem in drawing samples from the community, ensuring randomisation in the selection of the subjects. This article discusses the geographical stratification by socio-economic status used to draw a multistage random sample from a community-based elderly population living in a city like S. Paulo - Brazil. Particular attention is given to the fact that the proportion of elderly people in the total population of a certain area appeared to be a good discriminatory variable for such stratification. The validity of the stratification method is analysed in the light of the socio-economic results obtained in the survey. Em países como o Brasil é sempre problemático conseguir-se uma amostra populacional randomisada e representativa dada a inexistência de um catálogo atualizado e global da população residente na comunidade. Discute-se a metodologia de estratificação geográfica por nível sócio-econômico utilizada para conseguir uma amostra randomisada em múltiplos estágios de uma população de idosos residentes na cidade de São Paulo. O estudo aponta para o fato de a proporção de idosos na população total de uma determinada área da cidade ter se mostrado uma variável com poder discriminante do nível sócio-econômico da população. Discute-se a validade do método de estratificação a partir dos dados coletados no inquérito.